Beyond national economy-wide rebound effects: An applied general equilibrium analysis incorporating international spillover effects - Simon Koesler; Kim Swales; Karen Turner (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
This paper proposes that the national focus of energy 'rebound' studies should be extended to an international context in the presence of supra-national agreements such as EU 20-20-20. The potential for energy efficiency improvements in one nation to impact energy use in others means that national targets and actions cannot be considered independently. This paper develops a general equilibrium analysis of increased efficiency in productive energy use, identifying a range of channels through which spillover effects may be transmitted as a result of trade in goods and services. The results show that energy efficiency in one nation does impact energy use in others. However, the sectoral and spatial distribution of positive and negative effects depends on the nature of the efficiency improvement and factor supply conditions. In particular, changes in relative competitiveness and energy supply conditions act to dampen economy-wide rebound as the boundaries of the economy are expanded.
urn:nbn:de:bsz:180-madoc-366582
Keywords: D58; Q41; Q43; F18; Q56; 330; energy supply; energy demand; rebound effects; energy efficiency; general equilibrium; trade spillover